Dysfunction of ventrolateral striatal dopamine receptor type 2-expressing medium spiny neurons impairs instrumental motivation - Iku Tsutsui-Kimura (Nature Portfolio, 2017)
D2 receptor-expressing medium spiny neurons (D2-MSNs) are thought to suppress goal-directed behaviours. Here authors ablate D2-MSNs specifically in the ventrolateral striatum, and find that surprisingly, it leads to a reduction in goal-directed motivation in mice.